2020
DOI: 10.1038/s41598-020-72302-1
|View full text |Cite
|
Sign up to set email alerts
|

Revealing soil legacy phosphorus to promote sustainable agriculture in Brazil

Abstract: Exploiting native soil phosphorus (P) and the large reservoirs of residual P accumulated over decades of cultivation, namely “legacy P”, has great potential to overcome the high demand of P fertilisers in Brazilian cropping systems. Long-term field experiments have shown that a large proportion (> 70%) of the surplus P added via fertilisers remains in the soil, mainly in forms not readily available to crops. An important issue is if the amount of legacy P mobilized from soil is sufficient for the crop nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 48 publications
4
62
0
7
Order By: Relevance
“…Knowing the different P pools present in the environment should help guide the management of P containing wastes and soil amendments (Condron and Newman, 2011). However, it may take years to remove substantial amounts of the so-called 'legacy' phosphorus (Gatiboni et al, 2020;Havens and Thomas, 2005;Lou et al, 2018;Pavinato et al, 2020) out of the soil to the point where dissolved P in runoff is effectively reduced (McCollum, 1991;Meals et al, 2010;Zhang et al, 2004;Sharpley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the different P pools present in the environment should help guide the management of P containing wastes and soil amendments (Condron and Newman, 2011). However, it may take years to remove substantial amounts of the so-called 'legacy' phosphorus (Gatiboni et al, 2020;Havens and Thomas, 2005;Lou et al, 2018;Pavinato et al, 2020) out of the soil to the point where dissolved P in runoff is effectively reduced (McCollum, 1991;Meals et al, 2010;Zhang et al, 2004;Sharpley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Legacy P is essentially a result of the application of phosphorus in excess of plant requirements due to the use of fertilizer and manure that builds up in soils over decades [95,96]. Consequently, the legacy P at a given location is closely tied to the soil properties, land use/land cover, management practices, and temporal changes that occur in the latter two factors [97][98][99]. Typical approaches used in estimating terrestrial legacy P for informing quantitative models include mass balances, chemical analyses, and the phosphorus cycle [100].…”
Section: Land Usementioning
confidence: 99%
“…This study in Florida showed promising results as a viable way of mining legacy P through reduced fertilizer applications but could benefit from further research and development. Pavinato et al [99] discussed other practices from the perspective of legacy P, which includes soil amendments, crop rotation, efficient crop varieties, modern fertilizers, and inoculation with P solubilizing microbes, etc. Their suitability for the LOW conditions needs assessment, followed by incorporation into agricultural and urban BMPs programs.…”
Section: Implications For the Lake Okeechobee Watershedmentioning
confidence: 99%
“…Overall, it can be inferred that i) vegetation C is much more sensitive to fire than soil C pools, ii) high NPP cannot be seen as an indicator of the size of soil C pools in tropical ecosystems, and iii) fire suppression may benefit soil C pools, but it comes at a cost of reduced plant biodiversity (Abreu et al, 2017). Similarly, liming and fertilization to sustain intensive agriculture with multiple crops grown in succession under no-tillage (Pavinato et al, 2020) also should favor increasing soil C pools, particularly across the Cerrado. Based on the evidence gathered, in ecosystems where precipitation levels are low or suffer strong seasonality, high temperatures can override the control of MAP on EEM levels (Figure 2).…”
Section: Decreasing Precipitation Under Constantly High Temperaturesmentioning
confidence: 99%